Social economics. - Hagenbuch, Walter. (Cambridge economic handbooks., 1958)
Concerns with the problems of mankind in its ordinary everyday environment-with population, housing, working conditions, unemployment, poverty, social services, national insurance and assistance, and the welfare state.